Exosomes derived from TNF-α-treated bone marrow mesenchymal stem cells ameliorate myocardial infarction injury in mice - Shuo Wang; Rubing Wu; Qincong Chen; Tao Liu; Liu Li (Organogenesis, 2024)
Exosomes derived from bone marrow mesenchymal stem cells (BMSCs) exhibit considerable therapeutic potential for myocardial regeneration. In our investigation, we delved into their impact on various aspects of myocardial infarction (MI), including cardiac function, tissue damage, inflammation, and macrophage polarization in a murine model. We meticulously isolated the exosomes from TNF-α-treated BMSCs and evaluated their therapeutic efficacy in a mouse MI model induced by coronary artery ligation surgery. Our comprehensive analysis, incorporating ultrasound, serum assessment, Western blot, and qRT-PCR, revealed that exosomes from TNF-α-treated BMSCs demonstrated significant therapeutic potential in reducing MI-induced injury. Treatment with these exosomes resulted in improved cardiac function, reduced infarct area, and increased left ventricular wall thickness in MI mice. On a mechanistic level, exosome treatment fostered M2 macrophage polarization while concurrently suppressing M1 polarization. Hence, exosomes derived from TNF-α-treated BMSCs emerge as a promising therapeutic strategy for alleviating MI injury in a mouse model.